2015
DOI: 10.1016/j.jacr.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Patients Prefer Results From the Ordering Provider and Access to Their Radiology Reports

Abstract: Purpose: Imaging results are generally communicated to patients by referring providers. Directly communicating results has been suggested as a way for radiologists to add value, though few studies have investigated patients' preferences in this regard. The aim of this study was to determine patients' preferences for receiving their imaging results. Methods:In this institutional review board-approved study, adult outpatients undergoing CT or MRI at an academic medical center and an affiliated county hospital ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 20 publications
3
37
0
1
Order By: Relevance
“…10,11,13,[31][32][33] The majority of our participants wanted to learn results "as soon as possible" and wanted a written record much like adult patients. [6][7][8][9]34 Portals may meet those stated needs and caregivers recognized this.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11,13,[31][32][33] The majority of our participants wanted to learn results "as soon as possible" and wanted a written record much like adult patients. [6][7][8][9]34 Portals may meet those stated needs and caregivers recognized this.…”
Section: Discussionmentioning
confidence: 99%
“…Many adult patients want immediate access to test results . Portals are one way to move toward this.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that patients prefer to receive their test results from RPs rather than radiologists (2,(20)(21)(22)(23). However, the results of these studies should be interpreted cautiously because they do not involve a standardized method of conduct that includes factors such as the patients' educational and sociocultural background; anticipated delivery time of the test results; and the type of patient-radiologist encounter (i.e., interactive vs. noninteractive).…”
Section: Discussionmentioning
confidence: 99%
“…Patients also preferred detailed radiology reports, with some requesting access to key images. In a similar study of patients undergoing CT or MRI at an academic medical center (77%) or a county hospital (23%), among 617 surveys, 63% revealed preference for receiving results from their ordering providers; 64% desired access to their imaging report, and 85% wished to see their images (22). …”
Section: The Patient-centric Modelmentioning
confidence: 99%